Is a good relationship enough for a good life? - Xu, Efendy; Prihadi, Kususanto Ditto; Wulandari, Primatia Yogi; Adiati, Rosatyani Puspita; Cahyono, Rudi; Widayat, Iwan Wahyu; Indrijati, Herdina; Septarini, Berlian Gressy; Nisa, Valina Khiarin (Intelektual Pustaka Media Utama, 2023)
Satisfaction with life is an important element of mental health as its protective features against depression, anxiety, and other mental health problems. The bottom-up theory of life satisfaction explained that satisfaction in specific domains tend to sum up to general life satisfaction. accordingly, studies reported that relationship satisfaction predicts general life satisfaction This cross-sectional study aims to investigate the role of two variables, namely perceived social support (PSS) and mattering. We hypothesized that PSS and mattering perform full serial mediation on the link relationship between relationship satisfaction and life satisfaction. 256 individuals who live in several urban areas in West Malaysia were recruited through purposive sampling to respond to online form consisted of scales of relationship satisfaction, satisfaction with life, general mattering scale and multidimensional scale of perceived social support. Bootstrap method with 95% confidence interval and 5,000 samples was conducted through PROCESS Macro model 6; the results suggested that a significant, full serial mediation occurred. Additionally, both PSS and mattering significantly predicted life satisfaction after controlling for each other.